Pencegahan Penodaan Agama Perspektif Fiqh JinÃ¢yah - Habibullah, Ahmad (Prodi Hukum Pidana Islam Fakultas Syariâah dan Hukum Universitas Islam Negeri Sunan Ampel Surabaya, 2015)
Abstract: This article discusses the Islamic criminal Law (fiqh jinÃ¢yah) analysis on prevention of blasphemy in Indonesia. Law No. 1 Year 1965 concerning with prevention of religion abuse and/or blasphemy and Criminal Code which see criteria regarding the banned or misguided sects or organizations that are also stipulated in the provisions of MUI (Indonesian Ulama Council) in 2007. The laws state that the legal sanction against the perpetrators of the desecration of religion is imprisoned for ever five years. In Islamic criminal Law, the detailed criteria of blasphemy can only slightly be met due to the absence of the text of either al-Qurâan or al-Hadith that explain in detail about the legal sanction of blasphemy. Application of the legal punishment which based on the wisdom of judge can be used against blasphemy. Such a legal punishment is in line with the existing legal sanction in UUPNPS. This is when the offense of blasphemy committed is rated light. On the other hand, if the offense of blasphemy is considered very heavy and has a very great effect, it can be the opposite.Keywords: Blasphemy, legal sanction, Islamic criminal law.Â Abstrak: Artikel ini membahas tentang analisis fikih jinÃ¢yah tehadap pencegahan penodaan agama di Indonesia. Undang-Undang Nomor 1 Tahun 1965 Tentang Pencegahan Penyalahgunaan dan atau Penodaan Agama maupun KUHP, melihat kriteria mengenai aliran/organisasi yang terlarang atau sesat yang tertuang dalam ketentuan hukum tersebut yang dikuatkan pula oleh fatwa MUI pada tahun 2007, dinyatakan bahwa sanksi hukum terhadap pelaku penodaan agama adalah dengan pidana penjara selama-lamanya lima tahun. Dalam Fiqh JinÃ¢yah, kriteria penodaan agama secara terperinci dapat ditemui meskipun hanya sedikit, dikarenakan tidak adanya nash al-Qurâan maupun Hadis yang menjelaskan secara detail mengenai penodaan agama beserta sanksi hukumnya. Penerapan hukuman taâzÃ®r yang berdasarkan kearifan hakim, digunakan untuk menjerat pelaku penodaan agama. Hukuman taâzÃ®r ini sejalan dengan sanksi hukum yang ada dalam UUPNPS, hal ini bila delik penodaan agama yang dilakukan dinilai ringan. Tetapi di sisi lain akan sangat bertolak belakang, apabila delik penodaan agama dinilai sangat berat dan besar pengaruh yang ditimbulkan.Kata Kunci: Penodaan agama, sanksi, fiqh jinÃ¢yah.